Sulfamic acid: an efficient and cost-effective solid acid catalyst for the synthesis of alpha-aminophosphonates at ambient temperature - Mitragotri, Satish D.; Pore, D. M.; Desai, Uday V.; Wadgaonkar, P. P. (Catalysis Communications, 2008)
Sulfamic acid catalyzed solvent-free protocol has been developed for the synthesis of alpha-aminophosphonates by three component condensation between aldehydes, amines and diethyl phosphite at ambient temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophosphonates; diethylphosphite (DEP); solid acid catalyst; Solvent-free; sulfamic acid (SA)

Alum: an efficient catalyst for one-pot synthesis of alpha-aminophosphonates - Sonar, Swapnil S.; Shelke, Kiran F.; Kakade, Gopal K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
Alum (KAl(SO(4))(2)center dot 12H(2)O) is an inexpensive, efficient, non-toxic and mild catalyst for the one-pot synthesis of alpha-aminophosphonates. A three component reaction of an aldehyde/ketone, an an-tine and triethyl phosphite was carried out under solvent-free conditions to afford the corresponding alpha-aminophosphonates in short reaction times and high yields with the green aspects by avoiding toxic catalysts and solvents. (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Aldehyde/ketone; alpha-Aminophosphonates; Alum; Amine; Solvent-free; Triethyl phosphite

Alum catalyzed convenient synthesis of quino [2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives - Sonar, Swapnil S.; Sadaphal, Sandip A.; Shitole, Nana N.; Jogdand, Nivrutti R.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Bulletin of the Korean Chemical Society, 2009)
We have described an efficient synthesis of quino[2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives by the nucleophilic addition of triethyl phosphite to substituted quino[2,3-b][1,5]benzoxazepines promoted by easily available, inexpensive and mild catalyst KAl(SO(4))(2)center dot 12H(2)O (alum). The reactions proceed smoothly at room temperature under solvent-free reaction conditions and providing high yield of product in very short reaction time.
Keywords: 5]benzoxazepine; alpha-Aminophosphonate; Alum; Quino[2.3-b][1; Solvent-free; Triethyl phosphite

Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite

Microwave assisted convenient synthesis of quino[2,3-b][1,5]benzoxazepines - Sonar, Swapnil S.; Sadaphal, Sandip A.; Pawar, Shivaji S.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
A convenient synthesis of quino[2,3-b][1,5]benzoxazepines from substituted 2-chloroquinoline-3-carbaldehyde and 2-hydroxyaniline by using stable, non-toxic and inexpensive catalyst 1,8-diazabicyclo-undecan-7-ene (DBU)/silica gel is described. This method affords the quino[2,3-b][1,5]benzoxazepines under the influence of microwave irradiation (360 W) in solvent-free conditions within short reaction times (2-3 min), giving high yields of products (93-96%). (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: 3-b][1; 5]benzoxazepines; DBU/silica gel; Microwave irradiatiom; Quino[2; Solvent-free

Synthesis and in vitro study of 14-aryl-14H-dibenzo[a.j]xanthenes as cytotoxic agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Mujahid, Mohammad; Sehar, Irum; Saxena, Ajit K. (Bioorganic & Medicinal Chemistry Letters, 2009)
A simple and expedient method for the synthesis of a series of 14-aryl-14H-dibenzo[a.j]xanthenes is described through a one-pot condensation of beta-naphthol with aryl aldehydes catalysed by TaCl(5) under solvent-free conventional heating. The major advantages of the present method are: high yields, less reaction time, solvent-free condition and easy purification of the products. The synthesized 14-aryl-14H-dibenzo[a.j]xanthenes were evaluated against a panel of six human cancer lines of different tissues. Synthesized compound 30 showed IC(50) of 37.9 and 41.3 mu M against Colo-205 and 502713, respectively, whereas 3g showed IC(50) of 41.9 mu M against Colo-205. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; beta-Naphthol; condensation; Cytotoxicity; One-pot reaction; Solvent-free; Tantalum(V) chloride; Xanthenes

Mild, efficient, and regioselective monobromination of arylamines and phenols using [BBIm]Br-3 as a new reagent - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Synthetic Communications, 2010)
We report here an efficient method for the synthesis and characterization of the room-temperature ionic liquid 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3) (2) and its application as an efficient reagent and solvent for regioselective bromination of arylamines and phenols under mild conditions. The bromination was carried out in the absence of organic solvents, and in most cases, the only extraction solvent needed was water. The spent 1,3-di-n-butylimidazolium bromide (1) was easily recycled.
Keywords: Ionic liquid; monobromination; Regioselective; Solvent-free; [BBIm]Br3

Aromatic bromination of aldehydes and ketones using 1,3-di-n-butylimidazolium tribromide [BBIm]Br3 ionic liquids under solvent-free conditions - Borikar, Sanjay P.; Daniel, Thomas (Journal of the Iranian Chemical Society, 2011)
An environmentally benign and efficient process for the preparation of monobromo derivatives of aryl aldehydes and ketones was developed by simple and practical reactions of aryl aldehydes or ketones with 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3), as a brominating reagent under solvent-free conditions in very high yields. The process has several advantages: high conversions, short reaction time, mild reaction conditions, simple workup with good to quantitative yields and re-usable ionic liquid.
Keywords: Bromination; green chemistry; Ionic liquid; Solvent-free; [BBIm]Br-3

Convenient and efficient protocol for the synthesis of acylals catalyzed by bronsted acidic ionic liquids under ultrasonic irradiation - Borikar, Sanjay P.; Daniel, Thomas (Ultrasonics Sonochemistry, 2011)
The synthesis of acylals (1,1-diacetates) via the reactions of aldehydes with acetic anhydride was carried Out in 85-97% yields at room temperature under ultrasound irradiation catalyzed by the Bronsted acidic ionic liquid [bmpy]HSO(4). This method provides several advantages, such as solvent-free conditions, operational simplicity, higher yields, and reduced environmental consequences. The ionic liquid was recovered and reused. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Butyl-3-methylpyridinium hydrogen sulfate; 1-Diacetates; Acylals; Ionic liquid; Solvent-free; Ultrasonic irradiation

Supported copper triflate as an efficient catalytic system for the synthesis of highly functionalized 2-naphthol Mannich bases under solvent free condition - Dindulkar, Someshwar D.; Puranik, Vedavati G.; Jeong, Yeon Tae (Tetrahedron Letters, 2012)
Various heterogeneous catalysts (Lewis acid) have been prepared and screened for the synthesis of Betti bases in an attempt to reduce the environmental hazards associated with the conventional homogeneous Lewis acid system. And we found especially Cu(OTf)(2)center dot SiO2 catalyzes the three-component coupling of aldehyde, 2-naphthol, and alicyclic amine to generate Betti base with high efficiency under neat conditions without additional co-catalyst or additive in air. The reaction is not sensitive to water and occurs smoothly in water as well. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Betti bases; single-crystal XRD; Solvent-free; Supported copper triflate; Three-component coupling

Highly efficient catalyst derived from Ni-Fe-hydrotalcite for solvent-free O- or S-acetylation of alcohols, phenols and thiols at room temperature - Choudhary, Vasant R. (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2013)
Solvent-free O-acetylation of alcohols (including secondary and tertiary alcohols) and phenols and S- acetylation of thiols by acetyl chloride with high product yields at room temperature in a very short reaction period can be easily accomplished using a small amount of solid catalyst obtained from the decomposition (at 600 A degrees C) of Ni-Fe-hydrotalcite. Both the reactions are carried out at room temperature under solvent-free conditions. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity.
Keywords: Acetyl chloride; Alcohols; Ni-Fe- ht derived catalyst; O- and S-acetylation; Phenols; Solvent-free

Mechanistic approach for expeditious and solvent-free synthesis of alpha-hydroxy phosphonates using potassium phosphate as catalyst - Kulkarni, Makarand A.; Lad, Uday P.; Desai, Uday V.; Mitragotri, Satish D.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
An extremely simple, high yielding, highly rapid and solvent-free protocol has been described for hydrophosphylation of aldehydes using potassium phosphate as catalyst. Easy commercial availability of the reusable catalyst, operational simplicity at ambient temperature and avoidance of conventional work-up as well as purification procedure makes this solvent-free protocol a near-ideal synthesis. (C) 2012 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: alpha-hydroxy phosphonates; Hydrophosphylation; Potassium phosphate; Solvent-free

PD@SBA-15 Nanocomposite catalyst: synthesis and efficient solvent-free semihydrogenation of phenylacetylene under mild conditions - Bhuyan, Diganta; Selvaraj, Kaliaperumal; Saikia, Lakshi (Microporous and Mesoporous Materials, 2017)
Pd-0 nanoparticles (NPs) have been fabricated on SBA-15 using a facile, rapid and highly reproducible microwave-assisted reduction by solvent method. The as-synthesized Pd@SBA-15 nanocomposite was well characterized using low angle and wide angle XRD, TEM, FE-SEM, N-2 adsorption-desorption isotherm, FTIR, XPS etc. The Pd@SBA-15 nanocomposite act as an active, recyclable heterogeneous catalyst for semihydrogenation of phenylacetylene under solvent-free mild reaction conditions (303 K, atmospheric H-2). A maximum of 94.4% phenylacetylene conversion was achieved with very high selectivity for styrene (95.5%). Moreover, the used catalyst was recovered by centrifugation and reused up to four times without significant loss in their catalytic activity. This optimized reaction protocol for phenylacetylene was also well performed in case of various other alkynes with similar or better performance. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pd-0 nanoparticles; Phenylacetylene; SBA-15; Semihydrogenation; Solvent-free

Amino acid amide based ionic liquid as an efficient organo-catalyst for solvent-free knoevenagel condensation at room temperature - Burate, Pralhad A.; Javle, Balasaheb R.; Desale, Pranjal H.; Kinage, Anil K. (Catalysis Letters, 2019)
Ionic liquids of amino acid amide were synthesized and used as an efficient catalyst for solvent-free Knoevenagel condensation. Synthesized ionic liquids are an environmentally benign, inexpensive, metal free and plays the dual role of solvent as well as an efficient catalyst for Knoevenagel condensation. A wide range of aliphatic, aromatic and heteroaromatic aldehydes easily undergo condensation with malononitrile and ethyl cyanoacetate. The reaction proceeds at room temperature without using any organic solvent and is very fast with good to excellent yield. Additionally, the catalyst is easily separable and recyclable without loss of activity. [GRAPHICS] .
Keywords: Acrylonitrile; Amino acid amide; Cyanoacrylate; Ionic liquid; Knoevenagel condensation; Solvent-free

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free